2019
DOI: 10.5114/aic.2019.81705
|View full text |Cite
|
Sign up to set email alerts
|

The role of serial carotid intima-media thickness assessment as surrogate marker of atherosclerosis control in patients with recent myocardial infarction

Abstract: Introduction Despite percutaneous coronary intervention (PCI), patients after their first myocardial infarction (MI) are at high risk of ischemic event recurrence. Therefore, there is a need for objective markers of adequate atherosclerosis control, independent of prescribed pharmacotherapy and patients’ compliance. Such a potential indicator of major adverse cerebral and coronary event (MACCE) risk might be change in carotid intima-media thickness (CIMT), which indicates atherosclerosis growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Individual vascular risk factors such as diabetes, hypertension, smoking, dyslipidemia and metabolic syndrome are associated with the risk of a first and recurrent ischemic stroke [5-7, 13, 43]. A recent study has shown that a greater increase in carotid intima media thickness (IMT) was associated with an increased incidence of major adverse cerebral and coronary events [44]. Similarly, in the J-STARS (Japan Statin Treatment Against Recurrent Stroke) study, patients with the greatest baseline IMT were at the highest risk of recurrent stroke, which was partially ameliorated by treatment with pravastatin [45].…”
Section: Discussionmentioning
confidence: 99%
“…Individual vascular risk factors such as diabetes, hypertension, smoking, dyslipidemia and metabolic syndrome are associated with the risk of a first and recurrent ischemic stroke [5-7, 13, 43]. A recent study has shown that a greater increase in carotid intima media thickness (IMT) was associated with an increased incidence of major adverse cerebral and coronary events [44]. Similarly, in the J-STARS (Japan Statin Treatment Against Recurrent Stroke) study, patients with the greatest baseline IMT were at the highest risk of recurrent stroke, which was partially ameliorated by treatment with pravastatin [45].…”
Section: Discussionmentioning
confidence: 99%
“…21 Methodological limitations of this study notwithstanding, our expert panel recommends against serial CIMT measurements for CVD risk stratification especially when not meeting the threshold for diffuse plaque ($1.5 mm). We recognized that based on limited or anecdotal evidence, there may be value in serial CIMT measurements in the hands of some experts for research, 22,23 , monitoring of progression or regression in specific cases 24,25 , and as a potential tool to alter patient behavior. 26 Additionally, it is possible that over time, an individual patient may have a CIMT value that has increased to $1.5 mm, signifying the development of diffuse atherosclerotic plaque by our definition; however the clinical utility of such long term CIMT monitoring is not yet established.…”
Section: Clinically Significant Carotid Arterial Plaque or Cimtmentioning
confidence: 99%
“…Since atherosclerosis increases the risk of cardiovascular disease, and measurements can be performed noninvasively by carotid artery ultrasonography, this method should be included in screening algorithms for the prevention of cardiovascular events 35 . Gacon et al demonstrated the value of serial carotid IMT measurements as a surrogate marker of atherosclerosis control in patients with recent MI 36 . IMT has been consistently associated with CHD in previous research, but its clinical usefulness in predictive risk assessment is limited 37 .…”
Section: Discussionmentioning
confidence: 99%